Physical and Mechanical Properties of Finger-jointed Keruing and Meranti Board using Phenol-Resorcinol-Formaldehyde and Polyurethane-Reactive Adhesives as Truck Deck - Afrian Sayyidina Achmad; Dede Hermawan; Mahdi Mubarok; Jajang Sutiawan; Ryan Nata Wirasasmita (Journal of Sylva Indonesiana, 2026)
Finger-jointed (FJ) boards are widely used for truck decking applications that require high mechanical strength and dimensional stability. Keruing (Dipterocarpus spp.) and Meranti (Shorea spp.) are common tropical woods, yet comparative performance data using different adhesives remain limited. This study evaluated the physical and mechanical properties of Keruing and Meranti FJ boards bonded with phenol-resorcinol-formaldehyde (PRF) and polyurethane-reactive (PUR) adhesives. Boards were manufactured using a 2 cm finger profile, adhesive spread of 260–300 g/m², and pressing pressure of 50 kg/cm². Physical properties assessed included moisture content, density, water absorption, thickness swelling, and delamination, while mechanical properties comprised modulus of rupture (MOR), modulus of elasticity (MOE), and Janka hardness. The experiment followed a factorial completely randomized design with two factors: wood species and adhesive type. All specimens achieved moisture contents of 9–10%. Keruing exhibited higher density (0.88–0.99 g/cm³) than Meranti (0.67 g/cm³). PUR adhesive significantly enhanced mechanical performance, increasing MOR to 128.81 N/mm² in Keruing and 122.70 N/mm² in Meranti, corresponding to improvements of 29.1% and 47.9%, respectively, and increasing MOE to 101.98 N/mm² and 96.88 N/mm², representing gains of 51.1% and 74.0%. These values exceeded the minimum requirements of ASTM D5572:1999. In contrast, PRF adhesive improved dimensional stability, reducing thickness swelling to 2.82% in Keruing and 3.57% in Meranti and producing low delamination values of 0.88% and 0.25%, fully complying with JAS 1152:2007 (<5%). The adhesive type and wood species had no significant effect on hardness. The results indicate that PRF is more suitable for applications requiring durability and moisture resistance, whereas PUR is preferable for maximizing mechanical strength in truck deck materials.